ADOPTION OF SMART FARMING TECHNOLOGIES: A DEMOGRAPHIC AND TECHNOLOGICAL ANALYSIS - Khanna, Kanika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Smart agriculture has emerged as a transformative approach to addressing the twin challenges of food security and environmental sustainability in the face of a growing global population. In the midst of a growing global population and in the face of twin challenges of food security and environmental sustainability, smart agriculture has come to represent a novel approach to tackling these problems. Some of these advanced technologies being utilised in smart agriculture include: Internet of Things (IoT), Artificial Intelligence (AI), blockchain, and Big Data. These technologies permit greater precision in resource management, data driven decision making and the introduction of environmentally friendly practices. This research examines how demographic factors like age, education, location and farm size influence a farmer’s adoption of smart agricultural technology. Using a structured survey with a total of 150 participants, the study investigates the attitudes of farmers about five different aspects: Then there is technology efficiency, technology cost effectiveness, technology convenience use, environmental technology advantage, and adoption potential. These results pinpoint education as a huge influence, as farmers with postsecondary education were much more likely to adopt. There is also a very marked difference in the propensity of younger farmers to accept advances when compared with their older colleagues. The biggest environmental ones with highest marks shows a sincere accord with ecological benefits of smart technologies. On the other hand, high initial expense continues to be a great barrier, implying the need for financial incentives and subsidies. The goal of this research is to provide policymakers and industry stakeholders with ideas that may be implemented. In these recommendations, there are investments in education, digital infrastructure and targeted outreach initiatives to bridge gaps between demographic and geographical differences.